A phase field model of pressure-assisted sintering - Dzepina,B; Balint,D; Dini,D (Journal of the European Ceramic Society, 2019)
The incorporation of an efficient contact mechanics algorithm into a phase field sintering model is presented. Contact stresses on the surface of arbitrarily shaped interacting bodies are evaluated and built into the model as an elastic strain energy field. Energy relaxation through deformation is achieved by diffusive fluxes along stress gradients and rigid body motion of the deforming particles maintain contact between the particles. The proposed model is suitable for diffusion deformation mechanisms occurring at stresses below the yield strength of a defect-free material; this includes Nabarro-Herring creep, Coble creep and pressure-solution. The effect of applied pressure on the high pressure-high temperature (HPHT) liquid phase sintering of diamond particles was investigated. Changes in neck size, particle coordination and contact flattening were observed. Densification rates due to the externally applied loads were found to be in good agreement with a new theory which implicitly incorporates the effect of applied external pressure.